CSR and socially responsible investing strategies in transitioning and emerging economies - Kuna-Marszałek, Anetta; Kłysik-Uryszek, Agnieszka, 1978- (Advances in business strategy and competitive advantage., 2020)
"This book identifies the scale and scope of implementation of CSR and socially responsible investing strategies and standards in companies operating in different transition and emerging economies as well as assessing the global effects of these activities"--Provided by publisher.